You don't seem Filipino - Simangan, Jacqueline (Nanyang Technological University, 2024)
With globalization, immigration, and the internet, the crossover of cultures is far more commonplace than it ever has been. As a result, many people around the world have grown up with several cultures, known as Third Culture Kids or Cross-Culture Kids. You Don't Seem Filipino uses my personal story to reflect on the experience of being a Third Culture Kid. This graphic novel memoir delves into my perspective growing up in the Philippines and Singapore; covering my relationship with language, my experience adapting to a new culture, and the sense of loss many Third Culture Kids undergo.